Analysis of the Biophysical Environmental Impact of Sand Mining in Mawasangka District, Central Buton Regency - Gandri, La; Munara, Agil Aqshan Nor; Sudia, La Baco; Indriyani, Lies; Bana, Sahindomi; La De Ahmaliun (Journal of Soilscape and Agriculture, 2023)
The rise of illegal or unlicensed sand mining by irresponsible individuals has caused damage along the coast of Mawasangka District, Central Buton Regency. This study aims to identify the biophysical environmental impacts due to illegal sand mining in the coastal District of Mawasangka Buton and recommendations for post-sand mining land management. The method used in this study was direct observation to determine changes in the coastline and types of damaged vegetation, normalized difference vegetation index (NDVI) analysis to determine the density of vegetation on post-mining land, and measuring the depth of excavation. The results showed that there had been 321 m of beach abrasion and the types of vegetation damaged were coconut, acacisa and jaran wood trees. The results of the NDVI analysis show that non-green space around the mining area is 33.63 ha, while very low vegetation density is 41.91 ha, and low vegetation is 330.05 ha, while the rest is moderate and high vegetation covering 605.47 ha. Measurement of the depth of excavation ranged from 0.6 m – 2.3 m with good and moderate categories. Management of coastal post-mining land in the Mawasangkan sub-district is directed as pond land and revegetation.